Ferroic orders in two-dimensional transition/rare-earth metal halides - Ming An; Shuai Dong (APL Materials, 2020)
Since the discovery of graphene, two-dimensional materials with atomic level thickness have rapidly grown to be a prosperous field of physical science with interdisciplinary interest for their fascinating properties and broad applications. Very recently, the experimental observation of ferromagnetism in a Cr2Ge2Te6 bilayer and a CrI3 monolayer opened a door to pursue long-absent intrinsic magnetic orders in two-dimensional materials. Meanwhile, the ferroelectricity was also experimentally found in a SnTe monolayer and CuInP2S6 few layers. The emergence of these ferroic orders in the two-dimensional limit not only brings new challenges to our physical knowledge but also provides more functionalities for potential applications. Among various two-dimensional ferroic ordered materials, transition/rare-earth metal halides and their derivants are very common. In this Research Update, based on transition/rare-earth metal halides, the physics of various ferroic orders in two-dimensional materials will be illustrated. The potential applications based on their magnetic and polar properties will also be discussed.